Relationship of Primary Care Physicians' Patient Caseload With Measurement of Quality and Cost Performance - Nyweide, David J.; Weeks, Bill; Gottlieb, Daniel J.; Casalino, Lawrence P.; Fisher, Elliott S. (JAMA, 2009)
Context Sufficient numbers of patients are necessary to generate statistically reliable measurements of physicians' quality and cost performance. Objective To determine whether primary care physicians in the same physician practice collectively see enough Medicare patients annually to detect meaningful differences between practices in ambulatory quality and cost measures. Design, Setting, and Patients Primary care physicians in the United States were linked to their physician practices using the Healthcare Organization Services database maintained by IMS Health. Patients who visited primary care physicians in the 2005 Medicare Part B 20% sample were used to estimate Medicare caseloads per practice. Caseloads necessary to detect 10% relative differences in costs and quality were calculated using national mean ambulatory Medicare spending, rates of mammography for women 66 to 69 years, and hemoglobin A 1c testing for 66- to 75-year-olds with diabetes, preventable hospitalization rate, and 30-day readmission rate after discharge for congestive heart failure (CHF). Main Outcome Measures Percentage of primary care physician practices with a sufficient number of eligible patients to detect a 10% relative difference in each performance measure. Results Primary care physician practices had annual median caseloads of 260 Medicare patients (interquartile range [IQR], 135-500), 25 women eligible for mammography (IQR, 10-50), 30 patients with diabetes eligible for hemoglobin A 1c testing (IQR, 15-55), and 0 patients hospitalized for CHF. For ambulatory costs, mammography rate, and hemoglobin A 1c testing rate, the percentage of primary care physician practices with sufficient caseloads to detect 10% relative differences in performance ranged from less than 10% of practices with fewer than 11 primary care physicians to 100% of practices with more than 50 primary care physicians. None of the primary care physician practices had sufficient caseloads to detect 10% relative differences in preventable hospitalization or 30-day readmission after discharge for CHF. Conclusion Relatively few primary care physician practices are large enough to reliably measure 10% relative differences in common measures of quality and cost performance among fee-for-service Medicare patients.